The impact of gender in mentor-mentee success: Results from the Women's Dermatologic Society Mentorship Survey - Gloria Lin, MD, MS; Jenny E. Murase, MD; Dedee F. Murrell, MA, BMBCh, MD, FACD; Lucas Da Cunha Godoy, MSc; Jane M. Grant-Kels, MD (Wolters Kluwer, 2021)
Background: Mentorship can have a profound impact on the success and happiness of a mentee while also providing a sense of fulfillment and enrichment for the mentor. Both officially designated and spontaneously chosen mentors can be useful for protégés as they navigate through their training and professional work environment while striving to obtain the optimal work-life balance. Different genders can have variable experiences, in both their personal lives managing family obligations and their professional lives as dermatologists, which may affect the advice and guidance offered. Objective: We studied the impact of gender on the mentor-mentee relationship for both official and spontaneous mentorships through a voluntary survey with a focus on reported outcomes from the perspective of the mentee. Methods: Participants were selected through e-mail invitation via the Women's Dermatologic Society and program directors of the Association of Professors of Dermatology membership lists and given a link to the anonymous survey tool. The survey included 13 questions looking at official and spontaneous mentorships, the role of gender, and success in the dermatology field. Results: Of the 288 respondents, 202 (69.9%) were women, 86 (29.8%) were men, and one identified as other. Of the survey participants, 81% had official mentors and 91% had spontaneous mentors, with the overlap indicating that there may have been a history of multiple mentors per individual. Mentoring had an overall significant positive impact, and 98.5% of those in the spontaneous-mentor group rated the mentor as helpful compared with 87.6% in the official-mentor cohort. For official mentorships, 60.1% involved gender-similar mentors, and of those who had officially designated mentors of any type, 55% indicated a preference for mentors of the same gender. When specifically looking at respondents who participated in same-gender official mentorships, 65.5% preferred this type; of those who had a gender-dissimilar equivalent, only 36.7% indicated a preference for gender similarity in a mentor. Comparably, 59% of protégés with spontaneous mentors had a gender-similar one, and of those who had spontaneous mentors of any type, 59.2% preferred gender similarity. When considering only those in gender-similar spontaneous mentorships, 74.5% favored a same-gender pairing compared with 32.9% of those in the gender-dissimilar group. For female-female official mentorships, 75% preferred a female mentor, similar to 80.5% of the spontaneous-mentor cohort. Conclusion: Spontaneous mentors may provide a greater benefit than officially designated ones. For the majority of the categories, there was no statistical difference between female same-gender mentorships and gender-dissimilar relationships, which is in contrast with previously published literature. Overall, based on the feedback provided, the respondents believed that the quality of the relationship was the most important defining factor, but some noted that same-gender mentorships can provide additional benefit geared toward similar interests and experiences in life.